2015
DOI: 10.1007/s10896-015-9741-7
|View full text |Cite
|
Sign up to set email alerts
|

Using an Ecological Framework to Understand Men’s Reasons for Spousal Abuse: An Investigation of the Bangladesh Demographic and Health Survey 2007

Abstract: This article applies an ecological model to explore men's reasons for spousal abuse in Bangladesh. Data from the Demographic and Health Survey 2007 indicate that multiple factors perpetuate spousal abuse: the individual-level factors of low education and wealth, a micro-level factor of women making decisions regarding household purchases, an exo-level factor relating to the wives' failure to seek legal support, and a macro-level factor reflecting cultural support for using violence to control wives. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
3
18
0
1
Order By: Relevance
“…No que refere a descrição das características sociodemográficas da população estudada, identificou-se similaridade com os resultados encontrados por autores que realizaram suas pesquisas em instituições públicas, localizando os autores de agressão como pertencentes a classe menos favorecida da sociedade, com pouca escolaridade, exercendo atividade remunerada, com baixa renda e moradia em bairros populares (Akhter & Wilson, 2015;Dourado & Noronha, 2015; Gama, Bezerra, Silva, Vieira e Parente, 2014; Romagnoli et al, 2013;Romagnoli, 2015;Silva et al, 2014). Esses achados, porém, divergem do estudo realizado por Colossi e Falcke (2015), que teve como amostra uma população que se voluntariou para participar da pesquisa, onde a predominância foi de participantes que integram as classes sociais mais abastadas, com grande incidência de pessoas com grau superior de escolarização e renda até R$ 45.000,00.…”
Section: Discussionunclassified
“…No que refere a descrição das características sociodemográficas da população estudada, identificou-se similaridade com os resultados encontrados por autores que realizaram suas pesquisas em instituições públicas, localizando os autores de agressão como pertencentes a classe menos favorecida da sociedade, com pouca escolaridade, exercendo atividade remunerada, com baixa renda e moradia em bairros populares (Akhter & Wilson, 2015;Dourado & Noronha, 2015; Gama, Bezerra, Silva, Vieira e Parente, 2014; Romagnoli et al, 2013;Romagnoli, 2015;Silva et al, 2014). Esses achados, porém, divergem do estudo realizado por Colossi e Falcke (2015), que teve como amostra uma população que se voluntariou para participar da pesquisa, onde a predominância foi de participantes que integram as classes sociais mais abastadas, com grande incidência de pessoas com grau superior de escolarização e renda até R$ 45.000,00.…”
Section: Discussionunclassified
“…Carlson, 1984;Cummings, González-Guarda, & Sandoval, 2013;Han, Kim, & Tyson, 2010;Heise, 1998;Little & Kaufman, 2002;Tonsing, 2011). However, there have been some recent adoptions of the ecological framework to empirically analyze risk factors (e.g., Akhter & Wilson, 2016;Herrero et al, 2017). In the current research, we apply an empirical, ecological approach to provide more accurate information about the relevance of hostile sexism and attitudes toward IPV in predicting psychological aggression.…”
Section: An Ecological Approach To Investigating Ipvmentioning
confidence: 99%
“…Research suggests that social support is associated with a lower risk of further violence over a one-year period [7], lower incidence of depression and higher self-esteem [8]. Also, a recent study from Bangladesh showed that women who sought help from legal institutions experienced less violence from their husband [9]. Yet many women exposed to IPV do not seek help.…”
Section: Introductionmentioning
confidence: 99%